2011
DOI: 10.1007/dcr.0b013e3181fd48af
|View full text |Cite
|
Sign up to set email alerts
|

Single-Incision vs Straight Laparoscopic Segmental Colectomy: A Case-Controlled Study

Abstract: Single-incision laparoscopic colectomy is feasible and safe but takes more time than laparoscopic-assisted colectomy. Although results approximate those for laparoscopic-assisted colectomy, an additional learning curve is involved, and extra incisions are sometimes required. Single-incision laparoscopic colectomy requires further prospective validation so that the cost of the device can be justified by an improved clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
93
2
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(100 citation statements)
references
References 17 publications
2
93
2
3
Order By: Relevance
“…A number of reports have demonstrated its advantages in reducing the number of laparoscopic ports, including better cosmetic results, reduced postoperative pain and shorter recovery time (31)(32)(33)(34)(35). In the current study, no statistically significant differences in short-term outcomes were found between elderly colon cancer patients who underwent MLS and SLS.…”
Section: Discussioncontrasting
confidence: 47%
“…A number of reports have demonstrated its advantages in reducing the number of laparoscopic ports, including better cosmetic results, reduced postoperative pain and shorter recovery time (31)(32)(33)(34)(35). In the current study, no statistically significant differences in short-term outcomes were found between elderly colon cancer patients who underwent MLS and SLS.…”
Section: Discussioncontrasting
confidence: 47%
“…Some reports have successfully mentioned its advantages in reducing the number of laparoscopic ports, including better cosmetic results, reduced postoperative pain, and shorter recovery time. [13][14][15][16][17] To our knowledge, this is the first reported case of SILSþ1 TPE for advanced rectal cancer.…”
Section: Discussionmentioning
confidence: 72%
“…Another expected advantage of a small incision is the reduction of postoperative pain. None of the published reports assessed the postoperative pain or analgesic requirements (32)(33)(34)(35). Technical difficulties of single-access as the lack of triangulation and exposure, the inaxis view and conflicts between instruments are the most important challenges.…”
Section: Discussionmentioning
confidence: 99%